Influence of MIG Welding Process Parameters on the Strength of Bimetal Joints: Study of Gas Flow Rate and Macrofractures - Talifatim Machfuroh; Kris Witono; Septyana Riskitasari; Etik Puspitasari (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Bimetal joints are often used in various industries, such as automotive, power generation, electronics, and manufacturing. This is because bimetal joints allow the joining of two types of metal with different properties. Welding two different types of metal can pose its own challenges, such as the difficulty of controlling welding parameters so that the results are optimal for both types of metal, as well as differences in the thermal and mechanical properties of the two metals. This has led to extensive research on bimetal plate connections. Based on this background, this research aims to determine the effect of variations in flow rate and current strength on the tensile strength of robotic welding bimetal welded joints, as well as determine the results of macro photos of fractures resulting from tensile tests for each variation. The research was carried out experimentally where each variation was repeated with data 3 times. Based on the results and discussion, it is known that the optimal gas flow rate in general is 20 l/min, where the tensile strength reaches 353.1442 MPa–455.5458 MPa. At this flow rate, the dominant fracture occurs in the base metal and is ductile, which indicates good plastic deformation. On the other hand, gas flow that is too low or too high causes joint defects and reduces the tensile strength. Meanwhile, other welding parameters, namely variations in welding current, affect tensile strength. At a gas flow of 10 l/min, increasing the current to 180 A produces the highest tensile strength of 449.4357 MPa with ductile fracture characteristics. However, at a current of 120 A there is a significant decrease due to overheating, especially at higher gas flows such as 20 l/min and 30 l/min, which results in brittle fracture in the heat-affected zone (HAZ). The results of this research contribute to the understanding of the influence of welding parameters on the tensile strength and fracture characteristics of bimetallic joints. This research can be a reference for the development of more efficient and reliable welding processes in various industries, such as automotive, power generation and manufacturing, which require bimetallic joints with optimal quality.